Marcus inverted region of charge transfer from low-dimensional semiconductor materials - Junhui Wang (Nature Portfolio, 2021)
Marcus inverted region for charge transfer from low-dimensional semiconductor materials has been long sought after. Here, the authors reveal this region by directly measuring charge transfer from single-charge states rather than excitonic states.